Racism Presented in Colson Whitehead’s The Nickel Boys - Hamdani, Farizal; Cahyaning Rahayu, Anik (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This thesis is about racism that occurs in the novel The Nickel Boys by Colson Whitehead. The purpose of writing this thesis is to describe the types of racism and how the main characters Elwood and Turner struggle to face the acts of racism happening to them. This thesis uses an extrinsic approach, that is sociological approach to describe the text in the novel by connecting it to sociological theory. To analyze the types of racism, The theory of Carmichael and Hamilton identifies two forms of racism: individual racism and institutional racism. Individual racism happen includes behaviors that cause a person to experience death, injury, and denial of services. Meanwhile, institutional racism involves an institution that has a huge negative impact on access, services, and opportunities for minority groups. Individual racism occurs when black students experience violence that causes injury and death, such as the beatings and torture experienced by black students. Institutional racism occurs because of policies enacted at Nickel Academy that are detrimental to black students, such as behavioral differences between white and black students and poor facilities that are only experienced by black students. In the novel, it is mentioned that the individual and institutional racism experienced by black students resulted in their injuries, denial of services and even death. In the novel, it is found that the main character struggles to deal with racism by running away from Nickel Academy. Keywords: individual racism, institutional racism, racial acts, violence, struggle